Analisis Hubungan Antara Kelembaban Relatif Dengan Beberapa Variabel Iklim Dengan Pendekatan Korelasi Pearson di Samudera Hindia - Miftahuddin Miftahuddin; Ananda Pratama Sitanggang; Ichsan Setiawan (Jurnal Siger Matematika, 2021)
Relative humidity is a parameter that can affect global climate change, including in Indonesia region. Aceh province is located on the island of Sumatra and is located around the Malacca Strait in the northern and eastern parts of Aceh, while it is located around the Indian Ocean for the western and southern parts of Aceh. Thus, due to its geographic position Aceh Province has a considerable impact on climate change. Changes in relative humidity will cause changes in climate variables through natural cycles. There are several climate variables including air temperature, rainfall, sea surface temperature, wind speed, solar radiation, and dynamic altitude. In this study, the correlation method is used which aims to see the closeness of the relationship between each climate variable from in the Indian Ocean. Regarding climate variables having quantitative data, the Pearson Correlation method is used in this study. The results showed that the relationship between the variables air temperature and sea surface temperature had the highest relationship with a positive correlation value of 0.769. The lowest relationship is the variable rainfall and wind speed with a negative weak correlation value of -0.01. In correlation research, it shows that a gap in the dataset reduces the value of the positive correlation magnitude. The correlation value with gap tends to have a lower correlation coefficient value than the gapless correlation value in the dataset for positive correlation. Meanwhile, negative correlation applies the opposite. The existence of gaps can affect the distribution pattern, shape and slope of the data distribution so that it affects the correlation magnitude and direction (positive or negative).